تحليل نتائج سياسات الإنفاق العمومي في الجزائر - الفترة 2000- 2014- - عزوز, ميلود; خاطر, إسمهان (جامعة الوادي - University of Eloued, 2017)
شرعت الجزائر مع بداية 2001 في تطبيق حزمة من البرامج التنموية الضخمة الهادفة إلى إنعاش النمو الاقتصادي والتغلب على العوائق والنقص المسجل في الهياكل القاعدية وبيئة الاستثمار وزيادة التكامل بين قطاعات الاقتصاد المختلفة وإيجاد المحيط الملائم لاندماج اقتصادها في الاقتصاد العالمي،حيث تحاول هذه الورقة البحثية تحليل النتائج الاقتصادية المرتبطة بسياسة الإنفاق العمومي ضمن الأهداف الكبرى للسياسة الاقتصادية إجمالا . At the beginning of 2001, Algeria embarked on a series of major development programs aimed at reviving economic growth, overcoming obstacles and shortcomings in infrastructure and the investment environment, increasing the integration of different sectors of the economy and finding an appropriate environment for the integration of its economy into the global economy. Associated with public expenditure policy within the overall objectives of economic policy
Analysis of the results of public expenditure policies in Algeria 2000-2014
مقال
Keywords: الإنفاق العمومي، النمو الاقتصادي، برامج التنمية; public expenditure, economic growth, development programs